From quasi‐hereditary algebras with exact Borel subalgebras to directed bocses - Tomasz Brzezinski (Bulletin of the London Mathematical Society, 2020)
Up to Morita equivalence, every quasi-hereditary algebra is the dual algebra of a directed bocs or coring. From the bocs, an exact Borel subalgebra is obtained. In this paper a characterisation of exact Borel subalgebras arising in this way is given.